Prostaglandin E2 contributes to L. braziliensis survival and therapeutic failure in cutaneous leishmaniasis - Maurício T. Nascimento; Débora L. Viana; Fábio C. Peixoto; Sérgio M. Arruda; Edgar M. Carvalho; Lucas P. Carvalho (Emerging Microbes and Infections, 2023)
Patients with cutaneous leishmaniasis (CL) present an exacerbated inflammatory response associated with tissue damage and ulcer development. In recent years, higher rates of failure to pentavalent antimoniate therapy have been observed, yet the underlying reason remains poorly understood. We hypothesize that the eicosanoid PGE2 favours the establishment of infection by L. braziliensis, which contributes to therapeutic failure. The aim of the present study was to investigate the influence of PGE2 on the survival of L. braziliensis in macrophages and rates of therapeutic failure in CL patients. PGE2, an eicosanoid derived from the metabolism of arachidonic acid by the COX-2 enzyme, plays several roles in immune response. We found that increased PGE2 decreases the microbicidal function of macrophages and is associated with disease severity and therapeutic failure. Additionally, the neutralization of COX-2 by NS398, a selective NSAID, increases the ability of macrophages to kill L. braziliensis and protects against the pathological inflammatory response. Our data suggest that NS398 may serve as an adjunct treatment for CL patients.